(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2021)
Facilitating the development of socially relevant communicative skills in the secondary English language arts (ELA) classroom helps to guide the coursework towards personal relevance and usefulness for the students. It also encourages participation and engagement for students who might not find value in ELA content matter. This approach allows students to develop skills that are useful to them outside of the classroom: in their social lives, family relations and career navigations. Guiding their own personal voice through expressive writing and effectively sharing their ideas with others (through discussion formats and the instructor’s openness to student input) are the key components of this approach. This article expands upon the principles and methods an instructor can use to engage students and provide them with personal value in the ELA content matter.